The relationship between preimplantation morphokinetics of human embryos and sex chromosome pattern - Zeyad, Ali; Al-Abdulkareem, Bandar; Hammadeh, Mohamad Eid (Reproductive biology, 2018)
The aim of this study was to determine the relationship between the gender of human embryos and chronological changes during the two pronuclear (2PN) embryonic stage and blastocyst formation on day five after injection using time-lapse imaging and preimplantation genetic testing. A total of 120 couples who underwent intracytoplasmic sperm injection with preimplantation genetic testing were included in the study. Only normal embryos (n = 416) were enrolled in this study. Time-lapse imaging data of male (n = 227) and female (n = 189) embryo progression was carried out to estimate the times of initial appearance of the 2PN stage, fading times and day five blastulation rates. The results revealed that the 2PN stage (fertilisation) was reached significantly earlier in female embryos (9.09 ± 1.31 h) than in male embryos (9.52 ± 1.48 h, p-value = 0.0044). Conversely, the fading time of 2PN was significantly faster in male embryos (22.13 ± 2.02) than in female embryos (24.16 ± 2.61, p-value < 0.001). The blastulation rate was significantly higher in female than male embryos (68.25% vs. 57.71%; p-value = 0.025).